Enzymatic methylations: III. Cadaverine-induced conformational changes of E.coli tRNA(fMet) as evidenced by the availability of a specific adenosine and a specific cytidine residue for methylation(+) - Wildenauer, Dieter (1974)
A partially purified tRNA methylase fraction from rat liver, containing m(2)G- m(1)A- and m(5)C-methylase, was used to study the influence of Mg(++) and of the biogenic polyamine cadaverine on the enzymatic methylation of E.coli tRNA(fMet)in vitro. In presence of 1 or 10 mM Mg(++), guanosine no. 27 was methylated to m(2)G. In 1 mM Mg(++) plus 30 mM cadaverine, guanosine in position 27 and adenosine in position 59 were methylated. In presence of 30 mM cadaverine alone tRNA(fMet) accepted three methyl groups: in addition to guanosine no. 27 and adenosine no. 59 cytidine no. 49 was methylated. In order to correlate tRNA(fMet) tertiary structure changes with the methylation patterns, differentiated melting curves of tRNA(fMet) were measured under the methylation conditions. It was shown that the thermodynamic stability of tRNA(fMet) tertiary structure is different in presence of Mg(++), or Mg(++) plus cadaverine, or cadaverine alone. From the differentiated melting curves and from the methylation experiments one can conclude that at 37° in the presence of Mg(++) tRNA(fMet) has a compact structure with the extra loop and the TψC-loop protected by tertiary structure interactions. In Mg(++) plus cadaverine, the TψC-loop is available, while the extra loop is yet engaged in teritary structure (G-15: C-49) interactions. In cadaverine alone, the TψC-loop and the extra loop are free; hence under these conditions the open tRNA(fMet) clover leaf may be the substrate for methylation. In general, cadaverine destabilizes tRNA tertiary structure in the presence of Mg(++), and stabilizes tRNA(fMet) tertiary structure in the absence of Mg(++). This may be explained by a competition of cadaverine with Mg(++) for specific binding sites on the tRNA. On the basis of these experiments a possible role of biogenic polyamines in vivo may be discussed: as essential components of procaryotic and eucaryotic ribosomes they may together with ribosomal factors facilitate tRNA-ribosome binding during protein biosynthesis by opening the tRNA tertiary structure, thus making the tRNA's TψC-loop available for interaction with the complementary sequence of the ribosomal 5S RNA.